Comparison of physical activity in small-sided basketball games versus full-sided games - McCormick, B. T.; Hannon, J. C.; Newton, M.; Shultz, B.; Miller, N.; Young, W. (International Journal of Sports Science and Coaching, 2012)
Organized youth sports leagues attempt to meet many goals. Three primary needs for a youth sports league are to meet the participants' desires, provide quality learning experiences, and develop the competencies needed for continued participation. Possessing the ball, shooting more, and being more involved with a team's offense lead to more enjoyment and feelings of competence. Therefore, increasing the involvement of each player through more ball contacts should be a goal of youth sports leagues. Twelve male basketball players (age=15) from one high-school basketball team participated in this study. This study used paired t-tests to examine the differences between three-on-three basketball games and five-on-five basketball games that lasted for eight minutes in terms of average heart rate, moderate to vigorous intensity physical activity, vigorous intensity activity, and ball contacts. There were no significant differences between average heart rate, moderate-to-vigorous intensity activity, or vigorous intensity activity in the two conditions, but there were significantly more ball contacts on average in the three-on-three games. These results suggest that three-on-three leagues may be an appropriate sport for the initial exposure to basketball for youth players.